Coupled model for growth of dendrites and inclusions during solidification process of molten steel. (December 2013) - Li, Z. Q.; Yu, J. K.; Yuan, L.
Abstract : In this paper, a two-dimensional coupled model has been established to simulate the growth of dendrites and Al2 O3 inclusions during the solidification process of 30Cr2Ni4MoV molten steel. The simulation area was focused in a domain consisting of half of the primary dendrite arm spacing and the entire secondary dendrite arm spacing. The simulation results indicated that the degree of supercooling affected the growth of dendrites during the early stage, while the cooling rate affected the growth of dendrites during the middle and late stages. Both the degree of supercooling and the cooling rate exerted significant effects on the growth of the inclusions during the middle and late stages. The growth time of the dendrites increased with decreasing cooling rate. The final radius of inclusions increased with increasing degree of supercooling or decreasing cooling rate. The growth variable of the inclusions decreased with the increase in the original radius of the inclusions.